A software tool for network topology analysis under a Metabolic Engineering perspective - Pinto, José P. (2010)
In this work, we present a software application that runs as a plug-in over the OptFlux Metabolic Engineering platform allowing the topological analysis of metabolic networks. The major aim of this tool is to allow the interconnection between phenotype simulation tasks (using algorithms such as Flux Balance Analysis) and topological analysis of the same networks. The provided methods include node degree and degree distributions, shortest path analysis, clustering coefficients and several node rankers (betweenness and closeness centrality, hubs and authorities, etc). Also, it allows the creation of sub-networks through severalfilters, including some based on the results of phenotype simulation.